Disparity in Regional Development and its effect on Political Culture Trends: Evidence from Iran - Namaki, Azad; Fazeli, Mohammad; Ahmadi, Yaghoub (Studies of Transition States and Societies, 2021)
Seeking to determine the factors driving political cultures onto distinct trajectories, researchers have considered development one of the main causes for emerging new values, which configure political culture trends along with cultural heritage as a conservative force. We argue that if the theories are correct, then they should function not only at the national level but also at other levels. We found that disparate human development levels in Iranian provinces, as a result of the concentration of resources and wealth in some regions, are contributing to the diverse levels of emerging democratic values and attitudes across the country and among provinces, which in turn has driven the country to a cultural heterogeneity in terms of these new values. Furthermore, the inconsistent case of Kurds indicates that there is still room for the cultural heritages of small worlds to impose their forces on national political culture structure.